EFEKTIVITAS AMBULASI DINI PADA PERCEPATAN POLA BUANG AIR BESAR PADA IBU NIFAS DI RUANG SAKURA RSUD dr.SOEDOMO TRENGGALEK - Putri Sari Agustina; Nurdina Sulaimi Putra; Nur Yenny Hidajaturrokhmah (Universitas STRADA Indonesia, 2013)
Background : Defecation difficulties experienced by womens post partum is a problem faced by every postpartum woman. Some of the solutions that can be done to avoid difficulty in bowel movements. Mother should eliminate concern for bowel movements, one of which is do not be too scared if stitches will be open. Eat fibrous foods (vegetables and fruits) and drink plenty of water. If conditions permit, immediately get up and walk around or do early ambulation. Objective : Determine the effectiveness of early ambulation to the acceleration of defecation patterns on postpartum womans in the room Sakura dr. Soedomo public hospital. Methode: The study design was a quasy study of experimental post-test only control design. Population in this research is in the area of postpartum womans in Sakura room dr. Soedomo hospital some 40 people, 20 treatment group and 20 control group. The sample in this research is the spontaneous post partum womans in the room Sakura dr. Soedomo hospital existing at the time of the research. The sampling technique in this research is purposive sampling. The dependent variable in this research is early ambulation, and the independent variable is defecate pattern. Instrument is the questionnaire. Conclusion: If you experience difficulties or obstipations, do regular diet , plenty of fluids, fibrous food consumption, early mobilization. Result: Postpartum women treatment group early ambulation 9 (45 %) of respondents could do defecate on the third day, while the control group without early ambulation, there were 10 respondents (50 %) could defecate on the fifth day. Statistical test results obtained Independent sample t test results p=0.000 < 0.05. so stated that early ambulation effective against accelerated defecation patterns in postpartum women in the room Sakura dr . Soedomo hospital.